Modified netting technique for capturing gazelles in Serengeti, Ngorongoro and Loliondo, Tanzania. (20th November 2020) - Mdetele, Daniel; Misinzo, Gerald; Komba, Erick; Shemanche, Justin; Eblate, Ernest; Mdaki, Maulid; Keyyu, Julius; Kock, Richard
Abstract: During serological surveillance of peste des petits ruminants (PPR) disease, it required capture of randomly selected herds of gazelles as part of a study to determine the epidemiological role of these species in the circulation of peste des petits ruminants virus (PPRV). The study targeted capturing 135 Grant's gazelles ( Gazella granti ) from the Serengeti ecosystem, Tanzania. A modified netting technique was used aiming at providing safe, efficient and cost‐effective method for capture of gazelles. Locally available materials were used, and wildlife professionals guided the process of manufacturing supporting frame for the nets. Twenty (20) black metal pipes, 20 metal bars, four nets and three vehicles were used in the procedure. A total of 136 Grant's gazelles and nine Thomson's gazelles were captured in three missions. The Grant's gazelles were captured as per sample size calculated in all locations: Loliondo ( n = 25), Serengeti National Park ( n = 44) and Ngorongoro Conservation Area (NCA) ( n = 67) using less time and minimum cost than estimated. Injuries of three fawns (2%) inadvertently captured with the groups of adults and sub‐adult animals were recorded. Comparing with 2014 and other studies, modified netting technique showed high animal and operator safety levels with minimal injuries. With this technique, it was possible to capture even flighty animals that behave nervously because of hunting and other human activities, including Thomson's gazelles, a species previously found to be difficult to capture by netting. Résumé: Lors de la surveillance sérologique de la peste des petits ruminants (PPR), il a fallu capturer des troupeaux de gazelles sélectionnés au hasard dans le cadre d'une étude visant à déterminer le rôle épidémiologique de ces espèces dans la circulation du virus de la peste des petits ruminants (VPPR). L'étude visait à capturer 135 gazelles de Grant ( Gazella granti ) présentes dans l'écosystème du parc national du Serengeti, en Tanzanie. Une technique modifiée de capture par filets a été utilisée dans le but d'assurer une méthode sûre, efficace et économique pour la capture des gazelles. Des matériaux disponibles localement ont été utilisés et des experts de la faune ont guidé le processus de fabrication du cadre porteur des filets. Vingt (20) tuyaux en métal noir, 20 barres métalliques, quatre filets et trois véhicules ont été utilisés dans le cadre de la procédure. Au total, 136 gazelles de Grant et neuf gazelles de Thomson ont été capturées au cours de trois missions. Les gazelles de Grant ont été capturées selon la taille de l'échantillon calculée sur tous sites; Loliondo ( n = 25), parc national du Serengeti ( n = 44) et la zone de conservation du Ngorongoro (NCA) ( n = 67) en moins de temps et pour un coût minimum moins élevé que prévu. Trois faons (2%) capturés par inadvertance avec les groupes d'animaux adultes et subadultes ont été blessés. En comparaison avec l'année 2014 et d'autres études, la technique modifiée de capture par filet a démontré des niveaux élevés de sécurité pour les animaux et les opérateurs avec un nombre minimal de blessures enregistré. Grâce à cette technique, il a même été possible de capturer des animaux instables qui se comportent nerveusement en raison de la chasse et d'autres activités humaines, notamment des gazelles de Thomson, une espèce auparavant difficile à capturer au filet.